2022
DOI: 10.3389/fphar.2022.959938
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin activates the Caspase-3/GSDME pathway via ER stress induction of pyroptosis in lung cancer cells

Abstract: Pyroptosis is related to the occurrence, development, and therapeutic response of tumors, mediated by the proteins of the Gasdermin family. These proteins have become potential biomarkers for cancer treatment, and their agonists are likely to become a new direction in research and development of antitumor drugs. In this study, we found that myricetin has an inhibitory effect on lung cancer cells of the activation of pyroptosis. Analysis of the expression of Gasdermin family proteins revealed that this phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…According to the GO analysis, ER stress response-associated gene expressions were the most enriched. ER stress is known to mediate different modes of cell death, including autophagy, apoptosis, ferroptosis, and pyroptosis [47,48]. We detected the expression of p-IRE1α and CHOP increased in CT-treated A549 cells.…”
Section: Discussionmentioning
confidence: 83%
“…According to the GO analysis, ER stress response-associated gene expressions were the most enriched. ER stress is known to mediate different modes of cell death, including autophagy, apoptosis, ferroptosis, and pyroptosis [47,48]. We detected the expression of p-IRE1α and CHOP increased in CT-treated A549 cells.…”
Section: Discussionmentioning
confidence: 83%
“…Subsequent to the inhibition of caspase-12, there was a notable decrease in the expression levels of cleaved caspase-3 and cleaved GSDME. These results demonstrate that MYR induces lung cancer cell death mainly through pyroptosis induced by the ER stress pathway [ 127 ].…”
Section: Pyroptosismentioning
confidence: 95%
“…The results also demonstrated that GSDME and cleaved caspase-3 were significantly higher in the MYR-treated group compared to the untreated group. In summary, MYR may inhibit tumor growth and induce cell pyroptosis in vivo [ 127 ].…”
Section: Protective Effects Of Flavonoids Against Cancer: In Vivo Evi...mentioning
confidence: 99%
“…Transmission electron microscopy also revealed the existence of multiple pores, another hallmark of pyroptosis, with in cell membranes of myricetin-treated A549 cells and NCI-H446. When considered as a whole, the results show that myricetin causes pyroptosis in NCI-H446 and A549 cells by cleaving GSDME rather than GSDMD [103]. Cytotoxic potential of myricetin in A549 as well as A549-IR cells were examined.…”
Section: Lung Cancermentioning
confidence: 98%